DEVELOPMENT PROGRAM EVALUATION OF THE INDONESIA PROGRAM FOR GOLD MEDAL FOR SPORTS OF TENNIS - Yayan Rubaeni; James Tangkudung (Program Pascasarjana Universitas Negeri Jakarta, 2017)
This study aimed to evaluate the sport of tennis for The Indonesia Program for Gold Medal) or Program Indonesia Emas PRIMA), which is an evaluation study using model context, input, process, product and outcomes (CIPPO). Research shows that: 1) context evaluation is good – it has a purpose, the legal basis and the analysis of an adequate community; 2) Input evaluation is enough - has a mechanism of selection of athletes, coaches and managers, but need more socializations. The program needs some improvements such as; support facilities and infrastructure, national tennis training centre, adequate financial support, the necessity in involving the private and government enterprise; 3) Proccess evaluation is enough - planning and supervision of training has been well developed, but the implementation was not optimum, needs sport science embedded at the Team, and need more participation in international tournament; 4) Product evaluation is very bad - achievement of both as a Team and Individual athlete at the international multi event was not satisfied; 5) Outcomes evaluation is very good - this program provide more participation and opportunity for junior athletes. Therefore, I would like to recommend that this program should be extended with some improvement as research suggested.Keyword: Program Evaluation, CIPPO Model, The Indonesia Program for Gold Medal on Sport of Tennis.